Kinematic Analysis of Planar 5R Symmetrical Parallel Manipulator using an Interval Approach - Lara-Molina, Fabian; Koroishi, Edson (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
This paper addresses the analysis of the kinematics of the planar 5R parallel mechanism subjected to interval errors in the positioning of the active joints. Therefore, the kinematic model was formulated by including the interval errors. The complete kinematic model encompasses the forward, inverse, and workspace model. An interval approach based on the kinematic model was proposed to compute the position of the end-effector by taking into account the interval error. The results of the proposed interval approach show that it approximates better the interval error of the end-effector that the conventional interval analysis. The interval approach was compared to the response obtained with the Monte Carlo simulation.